Strategy of Insan Kamil in Building Green Education - Nurti Budiyanti; Asep Abdul Aziz; Mohamad Erihadiana (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2020)
The reality of life illustrates the low level of human concern on environment. In fact, it undeniably promotes environmental damage nationally and globally. Therefore, the ecosystem damage in various places and regions has become a serious threat to the survival of the life of the universe. Humans are closely related to nature and they have a great responsibility to protect the universe. In regard to this issue. This article provides an overview of the ideal human strategy, namely Insan Kamil, as a means of increasing awareness of our status as ‘Abdun and our role as caliph in instilling awareness of environmental love through Green Education. This study employed a qualitative approach in the form of literature study in collecting data. The result found that Insan Kamil is considered as a human who is trying to realize his status as a servant of Allah and his role as khalifatullah who has a Divine vision to worship Allah and they also have mission in maintaining natural order and prosperity of the environment. Through the approach of spiritual education, its strategy must be applied within family, school, and community. Thus, it is clear that the strategy of this Insan Kamil is not only in the scope of formal education, but non-formal and in-formal education must also have the same objective integration in order to foster awareness of environmental love through Green Education. Keywords: Strategy of Insan Kamil, Green Educaiton